Controlled release of thymosin β4 from injected collagen–chitosan hydrogels promotes angiogenesis and prevents tissue loss after myocardial infarction. (July 2012) - Chiu, Loraine LY; Reis, Lewis A; Momen, Abdul; Radisic, Milica
Aims: Acute myocardial infarction (MI) leads to fibrosis and severe left ventricular wall thinning. Enhancing vascularization within the infarct reduces cell death and maintains a thick left ventricular wall, which is essential for proper cardiac function. Here, we evaluated the controlled delivery of thymosin β4 (Tβ4), which supports cardiomyocyte survival by inducing vascularization and upregulating Akt activity, in the treatment of MI.Materials & methods: We injected collagen–chitosan hydrogel with controlled release of Tβ4 into the infarct after performing left anterior descending artery ligation in rats.Results: Tβ4-encapsulated hydrogel (thymosin) significantly reduced tissue loss post-MI (13 ± 4%), compared with 58 ± 3% and 30 ± 8% tissue loss for no treatment (MI only) and Tβ4-free hydrogel (control). Significantly more Factor VIII-positive blood vessels with diameter >50 µm were in the thymosin group compared with both MI only and control (p < 0.0001), showing Tβ4-induced vascularization. Wall thickness was positively correlated with the mature blood vessel density (r = 0.9319; p < 0.0001).Conclusion: Controlled release of Tβ4 within the infarct enhances angiogenesis and presence of cardiomyocytes that are necessary for cardiac repair. Original submitted 11 November 2011; Revised submitted 3 May 2012